Towards a global hub: The legal framework for dispute resolution in Malaysia’s Islamic finance industry - Oseni, Umar Aimhanosi; Ahmad, Abu Umar Faruq (Emerald Group Publishing Limited, 2016)
Purpose – The paper aims to examine significant developments in the institutional framework for dispute resolution in the Islamic finance industry in Malaysia. Malaysia, as part of its efforts to consolidate its enviable Islamic finance industry, has strengthened its institutional framework for dispute resolution. Design/methodology/approach – Data for this study were collected from both primary and secondary legal sources. Through a conceptual legal analysis, the institutional frameworks of dispute resolution in the Malaysia’s Islamic finance industry are studied. Findings – The study finds that Malaysia is far ahead of other jurisdictions by a significant margin in spearheading reforms in the emerging global Islamic finance industry. The dispute resolution framework has been largely affected by the recent reforms. Research limitations/implications – Other jurisdictions may borrow a leaf from Malaysia’s initiative in providing a robust legal framework for dispute management in the Islamic finance industry. Practical implications – Apart from adopting Malaysia’s framework and possibly adapting it to suit their specific local variations, other jurisdictions may also encourage Islamic financial institutions to incorporate effective dispute resolution processes in Islamic finance contracts. Originality value – This study critically discussed most recent developments in the institutional framework on dispute resolution in the Islamic finance industry in Malaysia.